Agrarism in Bulgaria and Czechoslovakia in the fi rst third of the 20th century: a comparative analysis - Kompaniiets, Oleksiy (Ukrainian Peasant, 2021)
Introduction. In the fi rst third of the 20th century the ideology of agrarianism reached the peak of its popularity in the countries of Central and Eastern and South-Eastern Europe, which was marked by the design of its numerous national variants: Bulgarian, Czechoslovak, Polish, Yugoslavic, Romanian, Ukrainian, Hungarian, German and Baltic. The experience of agrarianism in Bulgaria and Czechoslovakia seems especially interesting and valuable. It formed in different political and socio-economic conditions; in many cases these regional options were at the forefront of the agarist movement during the «golden age of the European peasantry» (according to the historian A. Toshkov, – period between world wars, when the «peasantry became a political entity, understood its destiny, realized its purpose and organized itself in defense of the third way, alternative to communism and capitalism»). Purpose is to fi nd out the causes and circumstances of the ideology of agrarianism in Czechoslovakia and Bulgaria, to carry out their comparative analysis, to fi nd out their European context. Results. The article offers a comparative analysis of the Bulgarian and Czechoslovak variants of European agrarianism of the fi rst third of the 20th century. The causes and circumstances of agrarianism in Bulgaria and Czechoslovakia are studied, as well as their national features are clarifi ed from the comparative perspective. The activities of political parties of agrarian orientation (Bulgarian Agrarian National Union and Republican Party of Farmers and Peasants in Czechoslovakia) were compared. Their activity at the international level – as a part of the International Agrarian Bureau (Green International) was also found out. Special attention was paid to the contacts between Ukrainian theorists and practitioners of agrarianism with their Czechoslovak and Bulgarian like-minded persons. The reasons and circumstances of the decline in the popularity of the ideology of agrarianism in Bulgaria and Czechoslovakia were explained. Conclusion. The uniqueness of the Bulgarian and Czechoslovak variants of agrarianism of the fi rst third of the 20th century was due to a number of circumstances and facts. Features of Bulgarian agrarianism: 1) the development of agrarian thought in Bulgaria was signifi cantly infl uenced by German and Russian agrarianism; 2) Bulgarian Agrarian National Union (BANU) is one of the oldest and most infl uential political parties of agrarian orientation in Central and Eastern and South-Eastern Europe; 3) the Bulgarian version is a classic example of the traditional version of agrarianism, focused on small and medium-sized peasants households; 4) Bulgarian agrarianism was the most radical variant of agrarian ideology, which, in contrast to the democratic tactics inherent in agrarianism, advocated the idea of establishing a dictatorship; 5) the ideology of Bulgarian agrarianism of the fi rst third of the 20th century had anti-urban, anti-Semitic and religious aspects; 6) Bulgarian agrarians were the fi rst among the agrarian parties of Central and Southeastern Europe to come to power (1919), but also lost it fi rst (1923); 7) BANU became the only agrarian party in Europe that ever came to power with a majority government, not just as part of a coalition. Features of Czechoslovak agrarianism: 1) the development of agrarian thought in Czechoslovakia was signifi cantly infl uenced by French agrarianism; 2) Czechoslovakia had the most developed industry (after Germany) in Central and Eastern Europe, and also had a relatively democratic political system, which created specifi c conditions for the development of agrarian ideology in the interwar period; 3) the agrarian parties of Czechoslovakia maintained strong positions in parliament and government throughout the interwar period; 4) the popularity of agrarianism in Czechoslovakia persisted until the end of the 1930’s, when in other countries of Central and Southeastern Europe it declined or disappeared; 5) Czechoslovak agrarianism of the interwar period was marked by the most extensive network of periodicals in Europe; 6) the Czechoslovak organization was the most powerful in the International Agrarian Bureau; 7) focused on farming, the Czechoslovak variant was one of the most moderate and most progressive variants of agrarianism; 8) at the turn of the 1920’s and 1930’s, active cooperation between Czechoslovak and Ukrainian agrarians was maintained, the most notable center of which was the Ukrainian Agrarian Society in Podebrady. Despite a number of differences and peculiarities of the program principles of the Bulgarian Agrarian National Union and the Czech Agrarian Party, their ideology was based on peasant centrism, as evidenced by the link between the political and socio-economic future of Bulgaria and Czechoslovakia and the peasantry/